Islam and Motivation to Quit Smoking: Public Health Policy Implications - Alturki, Khaled (Journal of religion and health, 2020)
In the WHO Eastern Mediterranean Regional Office some 14 years ago, a "religiously inspired approach" was proposed to combat tobacco use. This promoted a useful debate in the region. The purpose of this paper is to argue the need to identify the role which Islamic beliefs and teachings play (1) in influencing individual motivation to quit smoking and (2) in gaining support for public policies to reduce smoking. Ramadan and Hajj are taken as key points. These, it is argued, are times when Muslim religious motivation to abstain from smoking is strongest. This paper concludes that there is an insufficient evidence base on which to adopt a religiously inspired approach. All of civil society, including religious Muslim authorities, should rather supplement the efforts of health professionals to encourage smoking cessation.